The effectiveness of classroom management: 5 pivotal ingredients - St-Amand, Jerome (Special Education, 2018)
Gaudreau, N. (2017). Gérer efficacement sa classe: les cinq ingrédients essentiels. Québec (Québec): Presses de l’Université du Québec.